Inviting Small Children to Dialogue – Scaffolding and Challenging Conversational Skills - Bruce, Barbro (Educare, 2014)
The purpose of this study was to learn about how to scaffold and challenge conversational skills in children at an early stage in language development. Language production most often mirrors verbal comprehension, and moreover gives cues to the conversational partner to relate to and further expand upon. The presented results come from dialogues between speech and language therapists and children aged five to six whose language development has been found to be delayed for their age. However, the results are highly applicable to all children, particularly in small children during their most intensive language developing phases. The theoretical framework highlights the importance of being an active language learner, i.e. language skills are mastered by being used in social interaction. Twenty-two dialogues were video-, and audio recorded, transcribed and coded with respect to language structure and interaction. The mean number of words per turn in the children’s contributions was quantified and a qualitative analysis of the preceding turn of the elicitation strategies was performed. The results underline the importance of relating to the child’s focus without being soliciting, i.e. to comment and give feedback, rather than using many questions and imperatives.